The Effectiveness of the Duties and Authorities of Regional Heads in Handling Regional Losses in South Bolaang Mongondow Regency - Rahman, Mohammad Arif; Nur, Rafika; Rusmulyadi, Rusmulyadi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study discusses the effectiveness of the implementation of the duties and authorities of regional heads in handling regional losses in South Bolaang Mongondow Regency from the perspective of state administrative law. Based on the provisions of laws and regulations, especially Law Number 23 of 2014 concerning Regional Government and Government Regulation Number 38 of 2016 concerning Procedures for Claiming Regional Compensation for Non-Treasurer Civil Servants or Other Officials, regional heads have a central role in the process of settling regional losses. This study uses a normative juridical method with a legislative approach and concrete cases in the area. The results of the study show that the implementation of the duties and authorities of regional heads in handling regional losses has not run optimally due to structural constraints, weak internal supervision, and lack of understanding of the apparatus regarding the mechanism of claiming compensation. Therefore, it is necessary to strengthen implementing regulations, increase the capacity of apparatus, and optimize the function of regional inspectorates as part of the internal supervision system of local governments.